Measurement of fluid flow in closed conduits. Pressure differential devices. Method of measurement of pulsating fluid flow in a pipe, by means of orifice plates, nozzles or Venturi tubes Part 1.6, (15th March 1993) - British Standards Institution,
No abstract available